Cotranslational N-degron masking by acetylation promotes proteome stability in plants - Linster, Eric; Forero Ruiz, Francy Liliana; Miklánková, Pavlína; Ruppert, Thomas; Mueller, Johannes; Armbruster, Laura; Gong, Xiaodi; Serino, Giovanna; Mann, Matthias; Hell, Rüdiger; Wirtz, Markus (Nature Communications, 2022)
N-terminal protein acetylation (NTA) is a prevalent protein modification essential for viability in animals and plants. The dominant executor of NTA is the ribosome tethered Nα-acetyltransferase A (NatA) complex. However, the impact of NatA on protein fate is still enigmatic. Here, we demonstrate that depletion of NatA activity leads to a 4-fold increase in global protein turnover via the ubiquitin-proteasome system in Arabidopsis. Surprisingly, a concomitant increase in translation, actioned via enhanced Target-of-Rapamycin activity, is also observed, implying that defective NTA triggers feedback mechanisms to maintain steady-state protein abundance. Quantitative analysis of the proteome, the translatome, and the ubiquitome reveals that NatA substrates account for the bulk of this enhanced turnover. A targeted analysis of NatA substrate stability uncovers that NTA absence triggers protein destabilization via a previously undescribed and widely conserved nonAc/N-degron in plants. Hence, the imprinting of the proteome with acetylation marks is essential for coordinating proteome stability.
Gesehen am 30.03.2022